Plant Species Classification Based on Hyperspectral Imaging via a Lightweight Convolutional Neural Network Model - Liu, Keng-Hao; Yang, Meng-Hsien; Huang, Sheng-Ting; Lin, Chinsu (Frontiers in Plant Science, 2022)
In recent years many image-based approaches have been proposed to classify plant species. Most methods utilized RGB imaging materials and designed custom features to classify the plant images using machine learning algorithms. Those works primarily focused on analyzing single-leaf images instead of live-crown images. Without considering additional features of leaves’ color and spatial pattern, they failed to handle cases that contained leaves similar in appearance due to the limited spectral information of RGB imaging. To tackle this dilemma, this study proposes a novel framework that combines hyperspectral imaging (HSI) and deep learning techniques for plant image classification. We build a plant image dataset containing 1500 images of 30 different plant species taken by a 470-900nm hyperspectral camera and design a lightweight conventional neural network model (LtCNN) to perform image classification. Several state-of-art CNN classifiers are chosen for comparison. The impact of using different band combinations as the network input is also investigated. Results show that using simulated RGB images achieves a kappa coefficient of nearly 0.90 while using the combination of 3-band RGB and 3-band near-infrared images can improve to 0.95. It is also found that the proposed LtCNN can obtain a satisfactory performance of plant classification (kappa=0.95) using critical spectral features of the green-edge (591nm), red-edge (682nm), and near-infrared (762nm) bands. This study also demonstrates the excellent adaptability of the LtCNN model in recognizing leaf features of plant live-crown images while using a relatively smaller number of training samples than complex CNN models such as AlexNet, GoogLeNet, and VGGNet.